Osteoarticular complications in diabetes - literature review - Kinga Przyborowska; Beata Getka; Michał Łata; Katarzyna Wiejak; Mateusz Rukat; Justyna Kwiecień (Kazimierz Wielki University, 2024)
Due to the increasing number of patients suffering from diabetes mellitus scientists raise awareness of different symptoms that patients might present. The disease results from a defect in insulin secretion or action. Chronic hyperglycemia in diabetes causes damage and dysfunction of organs, especially the eyes, kidneys, nerves, heart and blood vessels. Diabetes can occur at any age and always requires treatment.  A common non-specific symptom of untreated DM may be osteoarticular complications. Typical symptoms of diabetes include polyuria, increased thirst, dehydration, weakness and drowsiness. Complications of the disease include eyes, kidneys, nerves, microangiopathies, diabetic foot syndrome, bones, joints, skin. In all patients, the most important thing is to control glycemia from the beginning of the disease